Psychoanalytic study on the main character in Nizami Ganjavi’s Layla Majnun And William Shakespeare’s Romeo Juliet: A Comparative Literature - Albab, Mohammmad Ulul (Instructional Development Journal, 2024)
Comparative literature is a branch of literary science that examines literature in various forms, functions, and meanings. This article tries to review from the aspect of Literary Psychology of two literature being compared, the novel "Layla Majnun" by Nizami Ganjavi and the movie "Romeo and Juliet" by William Shakespeare. The psychological theory employed is that of Sigmund Freud. According to psychoanalysis theory, there are three components of personality: Id, Ego, and Superego. The id contains all the inherited aspects of psychology, such as instincts, impulses, and drives. From this id come the ego and superego. The ego operates following the principles of reality. Meanwhile, the superego relates to the moral and ethical forces of the personality that operate, using idealistic principles, as opposed to the id and ego. It is used to examine the psychology of the main characters in the two literatures.